ISTILAH-ISTILAH DALAM EKONOMI ISLAM : UPAYA MEMPERKAYA KHAZANAH KOSA KATA BAHASA INDONESIA - Muhamad Musyafa' (Department of Indonesia Language and Literature Teaching, UIN Syarif Hidayatullah Jakarta, 2015)
Abstrac: Indonesia's relationship with Arab countries has existed since long ago. The relationship is well established in the field of trade and religious matters. Through its relationship, many benefits have been obtained to both Indonesia and Arab countries. Moreover, in the current time the Islamic economy has grown in Indonesia. The Islamic economy is developed from the Islam believes. The Islamic believes are mostly used Arabic. That is why many terms in the Islamic economics is derived from Arabic. Those terms some of them are absorbed in the Indonesian language. Therefore, the absorption of Arabic into Indonesian language course can be enriched Indonesian vocabulary. Some terms in the Islamic economics among them are a contract (agreement), “murābahah” (buying and selling), “musyārakah” (trade unions), “istisnā’” (buying and selling but the goods did not exist). Besides ‘aqad” (contract), there is also a term “ijrah” which has the same meaning, namely agreements. Although it has the same meaning, both are used in a different context. The word “akad” (contract) is an agreement between two or more persons with “ijab kabul” (agreement) based on the “syarak” provisions impacting object. Meanwhile, word “ijarah” is an agreement in terms of the lease. Finding those terms, it can be said that the decision of absorbing the Islamic economics terms attempting to enrich the Indonesian vocabulary. Abstrak: Hubungan Indonesia dengan negara Arab telah terjalin sejak dahulu. Hubungan tersebut terjalin baik dalam bidang perdagangan maupun keagamaan. Hubungan tersebut memberikan manfaat yang diperoleh baik oleh Indonesia maupun negara Arab. Terlebih lagi pada saat ini telah berkembang perekonomian Islam di Indonesia. Perekonomian Islam berkembang dari ajaran agama Islam. Ajaran Islam banyak yang menggunakan bahasa Arab. Untuk itu, banyak istilah dalam ekonomi Islam yang berasal dari bahasa Arab. Istilah-istilah tersebut beberapa diantaranya diserap di dalam bahasa Indonesia. Dengan begitu, terjadi penyerapan dari bahasa Arab ke dalam bahasa Indonesia yang tentu saja dapat memperkaya khazanah kosa kata bahasa Indonesia. Beberapa istilah tersebut ialah akad (perjanjian), murābahah (jual beli), musyārakah (serikat dagang), istisna’ (jual beli tetapi barang belum ada). Selain kata akad, terdapat juga istilah ijrah yang memiliki makna yang sama, yakni perjanjian. Meskipun memiliki makna yang sama, keduanya digunakan dalam konteks yang berbeda. Kata akad adalah perjanjian antara dua orang atau lebih dengan ijab kabul berdasarkan ketentuan syarak yang berdampak pada obyeknya. Sementara itu, kata ijarah adalah perjanjian dalam hal sewa menyewa. Melihat istilah-istilah tersebut, dapat dikatakan bahwa langkah penyerapan dalam bidang ekonomi Islam merupakan sebuah upaya untuk memperkaya khazanah kosa kata bahasa Indonesia. Permalink/DOI: http://dx.doi.org/10.15408/dialektika.v2i2.3625